Enhancing the competitive capacity of educational institutions in the era of change - Piatanom, Patumphorn (Frontiers in Education, 2025)
This article addresses a critical gap in educational leadership literature by moving beyond theoretical discussions of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) and BANI (Brittle, Anxious, Nonlinear, Incomprehensible) frameworks. It synthesizes empirical data, meta-analyses of educational competition, and findings from diverse institutional studies to build an evidence-based, actionable framework for enhancing institutional competitiveness. The proposed framework provides educational administrators with practical, structured guidance on strategic planning, technology integration, fostering resilient learning cultures, and navigating significant implementation barriers such as resource constraints and resistance to change. The article concludes that effective leadership in the era of change requires a deliberate balance between driving competitive advantage and cultivating institutional well-being and psychological safety.